Early Onset Drinking Predicts Greater Level But Not Growth of Alcohol‐Induced Blackouts Beyond the Effect of Binge Drinking During Emerging Adulthood. (8th February 2016) - Marino, Elise N.; Fromme, Kim
Abstract : Background: Early onset drinking is associated with later heavy drinking and related consequences. Early drinking onset and binge drinking are also independently associated with blackouts, which are periods of amnesia for events during a drinking episode. The objective of this study was to examine how early onset drinking relates to changes in the frequency of experiencing blackouts across 3 years controlling for year‐specific binge drinking. Methods: Participants ( N  = 1, 145; 67.9% female) from a 6‐year, longitudinal study are included in these analyses. Measures of self‐reported age at drinking onset included ages at first drink, first high, and first drunk, which were used to create a latent early onset drinking factor. Frequency of binge drinking and blackouts were assessed annually during Years 4 to 6. Results: Overall, 69.2% of participants reported experiencing blackouts. After controlling for year‐specific binge drinking, a growth curve model indicated that early onset drinkers reported more frequent blackouts at Year 4. There were, however, no significant effects of acceleration or deceleration in the frequency of blackouts across the 3 years. Early onset drinkers continued to experience more frequent blackouts compared with those who initiated alcohol use later, despite decreases in binge drinking over time. Conclusions: Early onset drinkers reported more frequent blackouts across all 3 years, indicating that early alcohol initiation predisposes those individuals to continue to experience more frequent blackouts, despite a decrease in their binge drinking. This may be due to various factors, such as altered hippocampal development and functioning resulting from early alcohol exposure. Abstract : Early‐onset drinkers both experienced more frequent blackouts at Year 4 and continued to experience greater levels of blackouts over time, but they did not exhibit differential growth or change in reported blackouts, despite the fact that the time‐varying effect of binge drinking on blackouts decreased across the three years. These findings indicate that there are likely unique neurobiological factors contributing to the experience of blackouts, such as altered hippocampal development and functioning resulting from early alcohol initiation. Notes : Covariate included in the model was sex; time‐varying covariates included in the model were year‐specific binge drinking. Frequency of alcohol‐induced blackouts is based on a Likert scale (1–5). Early, middle, and late categories represent −1 standard deviation (SD), the mean, and +1 SD of the latent early‐onset factor, respectively.